Experimental study of wear characteristics of Al2O3 reinforced magnesium based metal matrix composites. (2019) - Thirugnanasambandham, T.; Chandradass, J.; Sethupathi, P. Baskara; Martin, M. Leenus Jesu
Abstract: The present study deals with the wear characteristics of magnesium based metal matrix composites reinforced with alumina nano particles (50nm) under stir casting process. The wear test is conducted during dry sliding condition using pin on disc tester machine configuration with hardened steel counter-face, the load applied is 10N and 20N with different sliding speed (200, 400, 600 & 800 rpm) under the time intervals of 0-180 sec at room temperature. The wear decreases with addition of alumina nano particle under normal load at high sliding speed and also improves the co-efficient of friction from 0.095 to 0.55.